Pengelolaan Digital PR melalui Instagram @Dinkeskota.Bdg dalam Menyebarkan Informasi - Cempaka, Kirana Ayu; Fakhruroji, Mochammad; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the management of digital PR through Instagram @dinkeskota.bdg in disseminating information during the pandemic which refers to the concept of The Circular Model of Some for Social Communication. The method used in this study is a qualitative descriptive method with data collection techniques through observation and in-depth interviews. The results showed that the Public Relations of the Bandung City Health Office had implemented digital PR management through Instagram @dinkeskota.bdg in accordance with the concept of The Circular Model of Some for Social Communication proposed by Regina Luttrell with the following indicators: (1) Share stage; setting targets, and building public trust. (2) optimization stage; collaborate with other institutions that have high engagement and plan message delivery strategies. (3) management stage; resolve complaints quickly, conduct media monitoring and evaluation. (4) the engagement stage; fast responses (responding quickly) and reposting followers' content.